The early keyboard concertos in Ptuj - Eybl, Martin (De musica disserenda, 2008)
The 31 keyboard concertos now housed at the Knjižnica Ivana Potrča Ptuj represent a unique sample of early keyboard concertos in Central Europe, including works by the Viennese court composers Georg Christoph Wagenseil (1714-1777) and Wenzel Raimund Birck (1718-1763) as well as two musicians employed at the Graz parish church, Johann Michael Steinbacher (before 1710-after 1740) and Giovanni Antonio Sgatberoni (1708/09-1795). It is assumed that the Ptuj collection of keyboard music stems from the court of Count Joseph Bernhard von Attems, who resided at Dornava from 1754 to 1772. Considering the scribes and the paper quality of the sources, it seems possible that Steinbacher and Sgatberoni may have had a closer relationship to the Dornava court than has been assumed so far.
Keywords: glasba; music; 18.st.; koncerti za glasbila s tipkami; Gradec; Dunaj; Vienna; vodni znaki; prepisovalci